Local Authorities in Process of Modernization: Practice of the CIS Countries - A. I. Devyatkina (Московский журнал международного права, 2010)
The article deals with the issue of modernization of public relations in the orientation of interaction, consolidation, consensus of state and local administrations in subjects of the Russian Federation, Russia, another country-members of CIS, states of eastern and western Europe. Interpretation of factors and means of modernization of local administration is offered. Conclusions of necessity of transition from crisis and post crisis effects to modernization development of administration are made.